Ordered Variational Inequalities and Ordered Complementarity Problems in Banach Lattices - Jinlu Li; Ching-Feng Wen (Abstract and Applied Analysis)
We introduce the concepts of ordered variational inequalities and ordered complementarity problems with both domain and range in Banach lattices. Then we apply the Fan-KKM theorem and KKM mappings to study the solvability of these problems.